2021
DOI: 10.1091/mbc.e20-11-0705
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus actin-rearrangement-inducing factor ARIF-1 induces the formation of dynamic invadosome clusters

Abstract: The baculovirus  Autographa californica multiple nucleopolyhedrovirus (AcMNPV), a pathogen of lepidopteran insects, has a striking dependence on the host cell actin cytoskeleton. During the delayed-early stage of infection, AcMNPV was shown to induce the accumulation of actin at the cortex of infected cells. However, the dynamics and molecular mechanism of cortical actin assembly remained unknown. Here, we show that AcMNPV induces dynamic cortical clusters of dot-like actin structures that mediate degradation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…1e ). Our results were consistent with the finding that invadosome formation also requires the membrane-targeted C terminus of Arif-1 ( 16 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1e ). Our results were consistent with the finding that invadosome formation also requires the membrane-targeted C terminus of Arif-1 ( 16 ).…”
Section: Resultssupporting
confidence: 93%
“…A functional role of the C-terminal 200 amino acids for the Arif-1-induced actin changes was initially shown by infection studies with mutant AcMNPV lacking this domain ( 11 ). Recent expression studies of C-terminal truncations of Arif-1 have indicated that the transmembrane domains are also required for Arif-1 function and that the C terminus between residues 303 and 417 is at least necessary for the formation of invadosome clusters in S. frugiperda cells ( 16 ). Here, we expressed either the N- or C-terminal domain of Arif-1 in TN368 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauko et al . showed that baculovirus infection induces the formation of invadosome clusters potentially triggering an active degradation of ECM and Means and Passarelli reported a signalling cascade ultimately leading to rearrangement of the basal lamina upon baculovirus infection [ 48 , 49 ]. It is therefore tempting to speculate that baculoviruses actively downregulate the packaging of ECM components into EVs and thereby counteract the assembly and renewal of ECM layers, which might otherwise hamper systemic infection.…”
Section: Resultsmentioning
confidence: 99%
“…Arif-1 is expressed at the early stage of baculovirus infection and co-localizes with F-actin at the plasma membrane until late gene expression. It has been suggested that ARIF-1 induces the formation of invadosomelike structures, leading to the formation of organized structures to enable systemic viral spread [40]. The fast and early translocation of the nucleocapsids to the nucleus is critical for baculovirus replication.…”
Section: Baculovirus Entry and Transport Through The Cytoplasm Depend On Re-arrangement Of Host Cell Cytoskeletonmentioning
confidence: 99%